Virtual Communities and Customer Engagement as Determinants of Repurchase Intention among Mobile Legends Players in Indonesia - Dhani Miftakhul Zein (Westscience Press, 2026)
This study aims to analyze the effect of virtual communities on the repurchase intention of virtual products among Mobile Legends players in Indonesia, with customer engagement serving as a mediating variable. The research is grounded in the phenomenon of declining performance of Mobile Legends amid the global growth of the mobile gaming industry, which indicates the importance of virtual communities in fostering player engagement. Data were collected through a survey of Mobile Legends community members in East Java, with a sample of 160 respondents. The study employed a quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results show that virtual communities have a positive and significant effect on customer engagement and repurchase intention. Furthermore, customer engagement is proven to mediate the effect of virtual communities on repurchase intention. These findings confirm that effective management of virtual communities can enhance player engagement and encourage the sustainability of virtual product purchasing behavior in games.